PENGARUH VARIASI PARAMETER TERHADAP MATERIAL REMOVAL RATE DAN KEKASARAN PERMUKAAN STAINLESS STEEL 304 PADA PROSES CNC MILLING - Dimas putra utama; Eko Yudo; Erwansyah Erwansyah (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Large material removal rate and minimal surface roughness are the desired objectives in the CNC MORI SEIKI MV40–m process with the right process parameters to obtain a large material removal rate response and minimal surface roughness. The parameters used are cut speed, nutritional depth and spindle speed. The experimental design used based on the response surface methodology method in the form of a behnken design box. The experiment was randomized as many as 3 replications to produce more optimal results. The results showed that for parameters that contribute greatly to material removal rate and surface roughness is cutting speed and depth of cut. To obtain a large material removal rate, the cut speed is set at 143.28mm/min and the depth of cut is set at 0.25mm with a yield of 4.694mm3/minute. And to get the minimal surface roughness value, the cut speed is 118.05mm/min and the depth of cut is 0.15mm with a yield of 0.964 μm.